اشكالية صدمة الحداثة الادونيسية من القديم الى الحديث - عزيز, كيلاس محمد (Sulaimani Journal for Humanities, 2021)
Arab literature occupies a prominent position among modern literary genres, so interest in Arab literature expands and remains in dire need of criticism and description in order to rise and rise to higher levels. Contemporary poets achieve the uniqueness and distinction of their literary texts by investing all the technical tools that affected the contemporary literary writing methods until the word modernity emerged as a historical artistic phenomenon within the framework of its current situation and the extent to which it is related to the path of progress and modernization. Describe the style of variable functions and their mechanisms in studies related to this field.